[Milam's Colony settlement contracts]. - Milam's Colony (Tex.) (1835)
Settlement contracts for the colonization of Benjamin Rush Milam's colony in Texas. Contracts signed by Talbot Chambers, Milam's agent.
Online resource; title supplied by cataloger (LLMC Digital, viewed December 11, 2021).
Mansucript.
Keywords: Milam's Colony (Tex.); Coahuila and Texas (Mexico) -- Emigration and immigration; Texas -- Emigration and immigration -- 19th century